Translation and validation of the Arabic body image-acceptance and action Questionnaire-5 (BI-AAQ-5) for adults - Simona Abou Tayeh; Rabih Hallit; Diana Malaeb; Kamel Jebreen; Fouad Sakr; Mariam Dabbous; Souheil Hallit; Feten Fekih-Romdhane; Sahar Obeid (Journal of Eating Disorders)
Abstract Objective The Body Image-Acceptance and Action Questionnaire is a valid and reliable measure that assesses the extent to the degree of flexibility of an individual’s negative emotions and thoughts about their own bodies, and the extent to which they are able to engage in valued activity despite experiences of difficult body image internal. To date, there is no measure available and validated for Arabic-speaking adults for specifically assessing the concept of body image psychological flexibility. This study’s objective was to examine the psychometric properties of the Arabic version of the short 5-item form of the scale (BI-AAQ-5) in a sample of adults from Lebanon. Methods This study is cross-sectional, it enrolled 400 Arabic-speaking adults aged 18 and above using a snowball sampling technique (mean age: 25.93 ± 11.87 years and 65% females). The forward-backward translation method was adopted to obtain the Arabic version of the BI-AAQ-5. Psychometric properties were evaluated through confirmatory factor analysis (CFA), internal consistency analysis (Cronbach’s alpha and McDonald’s omega), and measurement invariance testing across sexes. Results The Arabic version of the BI-AAQ-5 demonstrated high internal consistency. The fit indices of originally proposed one-factor structure of the scale indicated that the measurement model fits the data well. The standardized estimates of factor loadings were all adequate. The results showed substantial evidence for configural, metric, and scalar invariance across male and female participants (males: 27.13 ± 6.96 vs. females: 25.73 ± 8.28; t(398) = 1.80, p =.074). Conclusion The BI-AAQ-5 translated into Arabic appears to be a valid self-assessment measure to evaluate body image acceptance among the adults. Findings suggest that the scale appears suitable for use among Arabic-speaking adults.